A Cluster-Based Distributed Hierarchical IDS for MANETs - B., Pahlevanzadesh; S.A., Hosseini Seno; T.C., Wan; R., Budiarto; M. Kadhum, Mohammed (2008)
Many attempts were made to secure wireless ad hoc networks, but due to special ad-hoc nature, which is lack of a fixed infrastructure and central management, finding an optimal and comprehensive security solution is still a research challenge.